Migrants from a Different Shore: Earnings and Economic Assimilation of Immigrants from China in the United States - Tony Fang; Mei Hsu; Carl Lin (Institute of Labor Economics (IZA), 2024)
Using data from 1980, 1990, and 2000 U.S. censuses, as well as the 2010 and 2019 American Community Surveys and the 1993–2019 National Survey of College Graduates, we investigate the performance of Chinese immigrants in the U.S. labor market over the past 40 years since China initiated its economic reforms and open-door policy in 1978. The results indicate that by 1990, Chinese immigrants' earnings surpassed those of immigrants from other countries, and by 2010, they exceeded the earnings of U.S.-born workers. Our Oaxaca-Blinder and Quantile decomposition analyses suggest that a significant portion of the earnings advantage held by Chinese immigrants, compared to other immigrant groups and U.S.-born workers over time, can be attributed to differences in observable characteristics, with education being the most crucial factor, both at the mean and across the earnings distribution. By employing national surveys that provide data on college graduates, we demonstrate that attaining the highest degree earned in the U.S. is associated with higher earnings for Chinese immigrants compared to all other immigrants. Furthermore, the difference in returns to U.S.-earned highest degrees can account for this earnings advantage.
Keywords: J31; J61; J24; 330; Oaxaca-Blinder decomposition; quantile decomposition; economic assimilation; the U.S.; China; immigration